Conflicts in Modern Families and Their Root Causes - Fatia, Maudy (Contemporary Society and Politics Journal, 2023)
The family is a group of people who join together as one because of blood ties and kinship. The more members there are in the family, the more opinions will be raised. Families are vessels for shelter, protection, spilling love, and sharing all sorrows as well. In the digital age, many families are affected by constant change and circumstances. That's when each opinion of the family members will clash and even tear each other down. It cannot be avoided by anyone because everyone is obliged to resolve it. This research is library research, which is a study that uses literature by examining books, and other sources of information that are relevant to the scope of the discussion. The results show that conflicts in modern families occur due to several factors, namely childcare patterns, family economy, and unequal domestic burdens. The lack of communication space between family members is also a cause of conflict in the family.